Subchronic toxicity and genotoxicity studies of Hericium erinaceus β-glucan extract preparation - S.N. Chen; C.S. Chang; M.F. Yang; S. Chen; M. Soni; B. Mahadevan (Current Research in Toxicology, 2022)
The medicinal effects of Hericium erinaceus have been long documented in scientific studies of Eastern traditional medicine. It is widely consumed, because of its nutritional qualities and perceived health benefits. Also, it is rich in β-glucans, which has been shown to have immunomodulating and antitumor effects. The objective of the present study was to investigate adverse effects, if any, of β-glucan extract preparation from H. erinaceus in subchronic toxicity and genotoxicity studies. The conduct of these studies was in compliance with Good Laboratory Practice (GLP) and test guidelines established by the Organization for Economic Cooperation and Development (OECD). In the subchronic toxicity study, Sprague Dawley rats (12/sex/group) were administered (gavage) H. erinaceus β-glucan extract preparation at dose levels of 0, 500, 1000 and 2000 mg/kg body weight (bw)/day for 90 days. Treatment with H. erinaceus β-glucan extract preparation did not result in any toxicologically significant treatment-related changes in clinical observations, ophthalmic examinations, body weights, body weight gains, feed consumption, and organ weights. Clinical pathology including hematology, serum chemistry, urinalysisand terminal necropsy (gross or histopathology findings) did not reveal any treatment-related adverse effects. The results of genotoxicity studies as evaluated by gene mutations in Salmonella typhimurium, in vitro chromosome aberrations and in vivo micronucleus test in mice did not reveal any genotoxicity of H. erinaceus β-glucan extract preparation. Based on the subchronic study, the no observed-adverse-effect level (NOAEL) for H. erinaceus β-glucan extract preparation was determined as 2000 mg/kg bw/day, the highest dose tested.